2004
DOI: 10.1590/s1516-635x2004000400006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chick weight, geometric mean diameter and sodium level in prestarter diets (1 to 7 days) on broiler perfomance up to 21 days of age

Abstract: Seven hundred and twenty Ross 308 chicks were raised in a controlled environment room, distributed in a factorial design with 3 hatching chick weights (37, 40 and 44 g), 3 geometric mean diameter (GMD) (0.561; 0.783 and 0.997 mm) and 4 total sodium levels (Na) (0.12; 0.24; 0.36 and 0.48%) in the pre-starter diet (1 to 7 days). From 8 to 21 days (d) one single basal diet was used for all treatments. The thirty seven-gram chicks had the smallest yolk sack weight at 4d, smallest body weight (BW) and feed intake (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…This effect can be related to the feed physical form, but also to the type of production envisaged. In the present study, the improvement observed in BW and FCR at 7 days of age was also reported by Ribeiro et al (2004) with feed particle size close to 0.8 mm. Similarly, Mingbin et al (2015) found feeding medium or coarse particle size diets caused a significant increase in broiler average daily gain and average daily feed intake during the starter phase.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This effect can be related to the feed physical form, but also to the type of production envisaged. In the present study, the improvement observed in BW and FCR at 7 days of age was also reported by Ribeiro et al (2004) with feed particle size close to 0.8 mm. Similarly, Mingbin et al (2015) found feeding medium or coarse particle size diets caused a significant increase in broiler average daily gain and average daily feed intake during the starter phase.…”
Section: Resultssupporting
confidence: 87%
“…Particle size of diet may have an impact on feed consumption and ingredient digestion as a result of changes in gastrointestinal tract structure and digestive secretions (Ribeiro et al 2004). In the current study, no marked effect of FI on the overall period was noted (P>0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maiorka et al (2004) observed a quadratic response for increasing Na levels (from 0.10 to 0.46%) in pre-starter diets on body weight gain (BWG), feed conversion ratio (FCR), FI and water consumption. Ribeiro et al (2004) suggested a wide range of Na levels, from 0.31 to 0.48%, in pre-starter diets for optimum performance. These results were similar to the earlier findings of Vieira et al (2003) who reported 0.38% and 0.40% Na for BWG and FCR respectively, for the first seven days of age.…”
Section: Dietary Electrolytes and Growth Performancementioning
confidence: 99%
“…According to some authors (Maiorka et al, 2004;Ribeiro et al, 2004), a higher Na level (over 0.40%) is optimal for water consumption, feed intake and body weight gain. Koreleski et al (2010) and Jankowski et al (2011b) recommend a lower Na level, 0.15% and 0.12%-0.17%, respectively, for starter diets, and 0.12%-0.16% and 0.11%, respectively, for finisher diets.…”
Section: Effect Of Dietary Na On the Growth Performance And Slaughtermentioning
confidence: 99%